2017
DOI: 10.1158/1055-9965.epi-16-0567
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Genetic Susceptibility to Breast Cancer in Women of African Ancestry

Abstract: Background Genome-wide association studies have identified ~100 common genetic variants associated with breast cancer risk, the majority of which were discovered in women of European ancestry. Due to different patterns of linkage disequilibrium, many of these genetic markers may not represent signals in populations of African ancestry. Methods We tested 74 breast cancer risk variants and conducted fine-mapping of these susceptibility regions in 6,522 breast cancer cases and 7,643 controls of African ancestry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…Therefore, we examined the association of the 10 SNPs identified in the present African ancestry GWAS of EOC or HGSOC at p < 1 × 10 −6 (Table ) with previously completed studies of breast cancer (overall, ER positive and ER negative) and prostate cancer in populations of African descent. Genetic associations in breast cancer were determined from 3,007 cases, of which 987 are ER negative and 1,518 are ER positive, and 2,720 African ancestry controls from the African American Breast Cancer Consortium (AABC), using the Illumina Human 1M‐Duo BeadChip . The genotype associations for prostate cancer were from 4,853 cases and 4,678 controls in the African American Prostate Cancer Consortium (AAPC), using the Illumina Infinium 1M‐Duo .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we examined the association of the 10 SNPs identified in the present African ancestry GWAS of EOC or HGSOC at p < 1 × 10 −6 (Table ) with previously completed studies of breast cancer (overall, ER positive and ER negative) and prostate cancer in populations of African descent. Genetic associations in breast cancer were determined from 3,007 cases, of which 987 are ER negative and 1,518 are ER positive, and 2,720 African ancestry controls from the African American Breast Cancer Consortium (AABC), using the Illumina Human 1M‐Duo BeadChip . The genotype associations for prostate cancer were from 4,853 cases and 4,678 controls in the African American Prostate Cancer Consortium (AAPC), using the Illumina Infinium 1M‐Duo .…”
Section: Methodsmentioning
confidence: 99%
“…Genetic associations in breast cancer were determined from 3,007 cases, of which 987 are ER negative and 1,518 are ER positive, and 2,720 African ancestry controls from the African American Breast Cancer Consortium (AABC), using the Illumina Human 1M-Duo BeadChip. 15 The genotype associations for prostate cancer were from 4,853 cases and 4,678 controls in the African American Prostate Cancer Consortium (AAPC), using the Illumina Infinium 1M-Duo. 16 For the selected SNPs, evidence of association from the studies of breast and prostate cancer is reported at a nominal level (p < 0.05) without adjustment for multiple comparisons.…”
Section: Examination Of Pleiotropy Of Gwas Snps Associated With Eoc Imentioning
confidence: 99%
“…Several studies have shown that combining risk estimates based on SNP genotypes with risk estimates from conventional breast cancer risk prediction tools, such as the BCRAT, can improve individual risk estimates for certain ethnic populations [ 13 16 ]. Larger studies have also made efforts to identify SNPs specifically associated with breast cancer risk in African American populations through consortium including the AMBER, ROOT, and AABC [ 17 , 18 ]. This approach clearly has important implications under current National Comprehensive Cancer Network guidelines for breast cancer screening and risk reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the correlations between the significant SNPs in our study and those in the GAME‐ON/DRIVE were very low ( r 2 < 0.1). Actually, it is common to identify different disease‐associated index SNPs between European‐ and African‐descent populations, and this phenomenon has been frequently reported in diseases including prostate cancer and breast cancer . This inconsistency of association may be due to the different genetic backgrounds, such as LD patterns between African and European ancestries.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, it is common to identify different disease-associated index SNPs between European-and African-descent populations, and this phenomenon has been frequently reported in diseases including prostate cancer [37][38][39][40] and breast cancer. 7,14,15,41 This inconsistency of association may be due to the different genetic backgrounds, such as LD patterns between African and European ancestries. In addition, although we undertook our GWAS using dense genotyping array with ∼2.5 million markers and imputation using the 1000 Genomes Project data, it is worth noting that rare variants (especially very rare ones) were not particularly targeted in array development or reliably imputed, and therefore not included in the analyses.…”
Section: Discussionmentioning
confidence: 99%